(untitled) (Archives of Criminology, 2014)
The cultural diversity of people serving custodial sentences in Poland is an issue that requires intensive research and analysis. In theory, the number of foreigners in Polish prisons might not seem great enough to warrant the interest of either researchers or practitioners. There are said to be around 500 such people (in custody and provisional detention) annually in a population of approx. 80,000. It has to be borne in mind, however, that the presence of people with a completely alien, and therefore often incomprehensible, cultural code in such a closed environment as a penal institution poses a great challenge, despite their small numbers. This article discusses the results of research conducted on foreigners in selected Polish penal institutions in 2014. The methodology involved analysing case files and conducting in-depth interviews with Prison Service officials and employees as well as the foreign prisoners themselves. These examinations attempted to determine, inter alia, the extent to which the cultural differences that incarcerated foreigners bring with them affect the status of foreigners serving custodial sentences and the way penal institutions function, and how well adapted the Polish prison system is to dealing with people from other cultures. One of the aspects discussed is the issue of accommodating foreigners given custodial sentences. This is analysed from the standpoint of possible cultural differences. According to the current legislation, foreigners are subject to the same rules as Polish prisoners when serving their sentences. The officials who were interviewed stressed that the rules for accommodating foreigners in detention centres and penal institutions are no different from those that apply to Poles – and nor should they be. As the interview progressed, however, these same officials would give examples of situations where the cultural differences of incarcerated foreigners affected e.g. the way they were accommodated in their cells and certain additional difficulties they had in adapting and relating to the prison subculture. Therefore, in practice, despite the lack of regulations and/or recommendations from above, these officials are forced to respond to the additional challenges resulting from the fact that foreigners do not speak Polish and exhibit behavioural patterns that differ to a greater or lesser extent from the norm. The experience and “penitentiary intuition” of the official actually turned out to be the only guide in these situations. The attitude of the foreign inmates themselves is no less important for the proper functioning of a penal institution. The examination shows that most of them are not looking for extra hassles but are trying to serve their sentences with as little trouble as possible. In view of the above, it would seem legitimate to argue that the main reason for there not being greater problems with foreigners in Polish prisons is that there are so few of them.